Electronic correlations for a two-level dimer: dynamical susceptibilities - Macedo, L. A.; Lagos, R. E. (Elsevier B.V., 2002)
The exact solution for the full electronic Hamiltonian for a two-level dimer is obtained. The parameter constellation (20) is reparametrized via orthogonal Slater atomic orbitals, yielding a three-parameter model. With the dimer embedded in a thermal bath, several temperature-dependent dynamical susceptibilities are computed. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: correlated electron systems; dynamical susceptibilities